EFFECTIVENESS OF INFORMATION SERVICES TO REDUCE STUDENT ACADEMIC PROCRASTINATION IN WORKING THESIS (EXPERIMENT STUDY ON STUDENT OF GUIDANCE AND COUNSELINGUNIVERSITAS PGRI PALEMBANG) - Ramadhani, Erfan; Putri, Ramtia Darma; Istiqoma, Vella Auliya (Jurnal Dosen Universitas PGRI Palembang)
ABSTRACKAcademic procrastination is an act of delays in doing a task. Based on the findings in the field, it was revealed that there are students who perform academic procrastination action. Procrastination is done in the form of a delay doing the thesis that has an impact on the completion of the study. The findings of this researcher into an indication that students have academic procrastination problems in doing thesis. One effort to solve the problem is by providing information services. This research uses quantitative method. This research type is experiment with one group pretest-posttest design. Research subjects amounted to 24 students of guidance and counseling courses above the eighth semester until academic year 2017/2018. The research instrument used Likert Scale model. Data were analyzed using Wilcoxon Signed Ranks Test with the help of SPSS version 20.00. In general, research findings indicate that information service is effective in reducing student academic procrastination in doing thesis. Specifically, 1) the level of student academic procrastination in doing thesis before being given treatment is in very high category; 2) the level of student academic procrastination in doing thesis after being given the treatment is in the high category; and 3) there is a difference or decreased level of student academic procrastination in doing thesis after given information service. Based on the results of this study can be suggested to the relevant parties in order to work together in helping to overcome the academic procrastination of students in doing thesis.Â Keywords: Academic Procrastination, Information Service.